Gendered Double Standards and Professional Inequality in Taylor Swiftâ€™s â€œThe Manâ€: A Liberal Feminist Analysis of SDG 5 - Salwa Salsabillah; T. Thyrhaya Zein; Amila Nirina Nasution; Maysa Lani; Hafidz Raskafi Lubis; Tengku Muhammad Zhafran Tsani Sinar (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study studies at how gendered double standards are portrayed in Taylor Swiftâ€™s song lyrics. â€œThe Manâ€ (2019). The study analyzes how similar social and professional activities are assessed differently depending on gender using a qualitative descriptive method and the theoretical framework of liberal feminism. The interactive model of Miles, Huberman, and SaldaÃ±a was used to examine the data, with a focus on thematic categories such sexual double standards and professional authority. The results show that similar activities, like romantic experience, financial assurance, and career aspirations, are socially valued when carried out by men but stigmatized when carried out by women. Furthermore, the study connects these poetic depictions to Target 5.5 of the United Nations Sustainable Development Goal 5 (SDG 5), which deals with womenâ€™s equalizer leadership opportunities. The study comes to the conclusion that popular music lyrics are important discursive tools that can promote global gender equity and critical awareness. Keywords: Liberal Feminism, Song Lyrics, Taylor Swift, SDG 5, Gendered Double Standard